2012
DOI: 10.1007/s40123-012-0002-z
|View full text |Cite
|
Sign up to set email alerts
|

Ophthalmic Complications of Dengue Fever: a Systematic Review

Abstract: IntroductionIn recent years there has been a spurt of peer-reviewed publications on the ophthalmic complications of dengue fever. The authors aim to review the ocular manifestations, utility of relevant diagnostic tests, management, prognosis, and sequelae of dengue-related ocular complications.MethodsA comprehensive literature search was conducted on Medline, PubMed, and Google Scholar databases. Only articles published or translated into the English language were considered, and key data from the full articl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
105
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(123 citation statements)
references
References 28 publications
4
105
2
1
Order By: Relevance
“…To date, there is no evidence as to which is the more superior mode of administration. However, the outcome of treatment with systemic steroids in vision in both forms has been favourable [6,7]. We commenced treatment with oral prednisolone in our patient due to the extensive involvement of the retina on OCT and also significant reduction in the initial visual acuity.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…To date, there is no evidence as to which is the more superior mode of administration. However, the outcome of treatment with systemic steroids in vision in both forms has been favourable [6,7]. We commenced treatment with oral prednisolone in our patient due to the extensive involvement of the retina on OCT and also significant reduction in the initial visual acuity.…”
Section: Discussionmentioning
confidence: 95%
“…There is no specific treatment for systemic dengue fever and usually supportive therapy is revolved. Most of the time, the course of the ocular complications, like systemic dengue fever, is generally self-limiting and resolves spontaneously even without treatment [4][5][6]. The improvement in visual signs and symptoms usually corresponds to improvement of platelet levels [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Lately, few isolated case reports have shown that the ophthalmic complications of dengue fever are not as rare as used to be thought before. [3][4][5][6][7][8][9] Any dengue fever patient with complaints of blurring of vision, floaters, scotomas or metamorphopsia must be thoroughly examined. Hereby, we present a case of a young girl with post dengue fever vasculitis and macular edema.…”
Section: Introductionmentioning
confidence: 99%